Smart-Valleys: a locally led adaptation solution enhanced inland valleys ecosystem services in Benin - Akodekou, A.D.; Dossou-Yovo, E.R. (2025)
Inland valleys are critical freshwater wetlands in Sub-Saharan Africa, providing multiple ecosystem services while supporting climate-sensitive production. As climate variability intensifies, locally led adaptation (LLA) approaches are increasingly recognized as essential for sustaining both livelihoods and ecosystems. This study assesses the Smart-Valley system—developed through collaboration between AfricaRice and local communities—as a locally led adaptation solution and evaluates its performance in enhancing ecosystem services relative to other types of inland valleys in central Benin. Using a mixed-methods approach, qualitative data from 41 focus group discussions and quantitative survey data from 298 farmers were analyzed to assess perceived ecosystem services, disservices, and threats across management approaches. Smart-Valleys operationalize LLA principles by embedding farmer decision-making in the design, construction, and collective management of low-cost water control infrastructure, enabling context-specific and adaptive responses to climate variability. Results show that Smart-Valleys significantly enhanced ecosystem service delivery compared to other systems. Provisioning services increased by 1.1–1.3 times, regulating services (including flood mitigation and disease control) by 1.03–1.4 times, and supporting services such as habitat conservation by 1.17–1.32 times. At the same time, Smart-Valleys reduced the perceived severity of major climate-related threats, particularly drought and flooding, through improved local water control and collective governance. However, cultural services were perceived to be lower in Smart-Valleys, highlighting trade-offs between agricultural intensification and socio-cultural values. Socio-economic factors, including gender, education, and income, significantly shaped farmers valuation of ecosystem services, underscoring the importance of inclusive and context-specific adaptation strategies. Overall, the findings demonstrate that Smart-Valleys function as an effective locally led adaptation pathway in inland valleys, enhancing ecosystem services and reducing climate-related risks while introducing manageable operational challenges. These results provide empirical evidence to support the scaling of Smart-Valleys as a climate-resilient, ecosystem-based, and community-driven approach aligned with multiple Sustainable Development Goals.